If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(a + 6) = -96 Reorder the terms: -8(6 + a) = -96 (6 * -8 + a * -8) = -96 (-48 + -8a) = -96 Solving -48 + -8a = -96 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + -8a = -96 + 48 Combine like terms: -48 + 48 = 0 0 + -8a = -96 + 48 -8a = -96 + 48 Combine like terms: -96 + 48 = -48 -8a = -48 Divide each side by '-8'. a = 6 Simplifying a = 6
| 10=7x+4-4x | | (200x^2)-9000x+98938=0 | | f(x)=(2x-1)3 | | 6m+6(3m-1)=m | | -2+14=12x-5-11x | | -4x=19-(-17) | | 6m+6(3m-1)=6m | | 2x-9=-3(x-6) | | 4p+5p=3 | | 5a+7a=100 | | 6(x+7)-7= | | x=90-x-24 | | 4p-5p=3 | | x-2y-3x+5y= | | (200x^2)-9000x-98938=0 | | -9(y+5)+6(y+8)=27 | | 2(4m-10)=-12m-40 | | -3x+7x-1= | | C-d=-2ford | | -8a=1 | | 2x+3(4-1)=2(5x+3)+4x | | 6x-4=31-x | | 6x=-360 | | 10x^2-3x-5=0 | | 0=-x^4+13x^2-36 | | sqrt(8)=2sqrt(2) | | 6x+7-2x+4=(-3x-5)-17 | | 3(x-1)-18= | | 2x+3(4-1)=2(5x+3)+4 | | 3(1c-2)=2(1c-6) | | 3x-8x-5=0 | | 3(x-1)-18=o |